Case Report : Mr. I 56 years old with Stroke Non Hemoragic - Akhlish Dzikrullah Ahmad; Agung Ikhssani; Muhammad Fitra wardhana (Jurnal teknologi Kesehatan Borneo, 2021)
Stroke is one of the most common diseases that cause functional impairment and disability. Stroke is the second leading cause of death and the leading cause of disability worldwide. Its incidence is increasing as the population ages. In addition, more young people have strokes in low- and middle-income countries. Data in Indonesia shows that stroke is the third most common cause of death, followed by diabetes mellitus and hypertension with a mortality rate of 138,268 people or 9.7% of the total deaths. Indonesia has a double burden in dealing with health problems. Lacunar strokes, a type of ischemic stroke, are small and located in non-cortical areas. Lacunar infarctions are caused by occlusion of small branches penetrating within the cerebral vessels of the circle of Willis, including branches of the middle cerebral artery, anterior cerebral artery, posterior cerebral artery, or spinal cord. basilar artery. The principle of treatment for acute lacunar stroke is very similar to that of acute ischemic stroke. The initial goals of acute stage treatment are to ensure medical stability and determine candidacy for thrombolysis. Tissue plasminogen activator (TPA) improves outcomes for patients with ischemic stroke. Once intracerebral hemorrhage has been ruled out, intravenous thrombolysis is an important step in treatment. Acute lacunar infarction is efficiently treated with TPA. This case report discusses a 56 year old Mr I diagnosed with a non-hemorrhagic stroke.